2016
DOI: 10.1371/journal.pone.0149574
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Administration of Benzo(a)pyrene Induces Memory Impairment and Anxiety-Like Behavior and Increases of NR2B DNA Methylation

Abstract: BackgroundRecently, an increasing number of human and animal studies have reported that exposure to benzo(a)pyrene (BaP) induces neurological abnormalities and is also associated with adverse effects, such as tumor formation, immunosuppression, teratogenicity, and hormonal disorders. However, the exact mechanisms underlying BaP-induced impairment of neurological function remain unclear. The aim of this study was to examine the regulating mechanisms underlying the impact of chronic BaP exposure on neurobehavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 52 publications
3
13
0
Order By: Relevance
“…In our study, SH-SY5Y cells when exposed to B[a]P induced oxidative stress as demonstrated by the significant increase of S phase cell accumulation and by the activation of the B[a]P metabolites to the antioxidant responses. In the present study, we found exposure to B[a]P in SH-SY5Y human neuroblastoma cell lines causes cell cycle arrest leading to increase proportion of cells at S phase and it finds support from previous reports [42,43,44]. Hence, it seems possible that oxidative stress may represent an important component in the mechanism of action of B[a]P-induced DNA damage in SH-SY5Y cell lines.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study, SH-SY5Y cells when exposed to B[a]P induced oxidative stress as demonstrated by the significant increase of S phase cell accumulation and by the activation of the B[a]P metabolites to the antioxidant responses. In the present study, we found exposure to B[a]P in SH-SY5Y human neuroblastoma cell lines causes cell cycle arrest leading to increase proportion of cells at S phase and it finds support from previous reports [42,43,44]. Hence, it seems possible that oxidative stress may represent an important component in the mechanism of action of B[a]P-induced DNA damage in SH-SY5Y cell lines.…”
Section: Discussionsupporting
confidence: 91%
“…Previous reports suggested that B[a]P exposure leads to cell cycle arrest with significant increase in the number of cells in S-phase of cell cycle [41,42]. Importantly, from late S phase to mitotic onset, the two fully duplicated centrosomes exhibit enhanced recruitment of pericentriolar material components that are essential for microtubule nucleation, a process termed centrosome maturation [41].…”
Section: Discussionmentioning
confidence: 99%
“…B[a]P can reach the encephalic central nervous tissues by crossing the blood–brain barrier [ 75 , 76 , 77 ]; this leads to increase nervous oxidative stress in the nervous system which in turn resulting in behavioral changes and alterations to the expression of antioxidant enzymes (e.g., superoxide dismutase, catalase and glutathione peroxidase and cellular lipid peroxidation [ 77 , 78 ]. Epidemiological studies have demonstrated that exposure to B[a]P causes neurological abnormalities such as cognitive impairment, learning difficulties, parasympathetic dysregulation and short-term memory loss [ 79 , 80 , 81 ]. Embryonic B[a]P exposure increases the risk of neural hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…In order to study effects of environmental pollutant BaP on AD development, we chose a chronic dosing paradigm (daily intraperitoneal injection for 2 months) and a relatively low dose of BaP (1 mg/kg/ bw/day). The dose was chosen based on the environmental/occupational exposure dosage and previous studies [11,13,14]. Vehicle groups were received with equal volume of corn oil (50 μl).…”
Section: Animals and Treatmentsmentioning
confidence: 99%
“…Epidemiological studies have shown that BaP exposure is associated with learning and memory deficits in healthy adults and coke oven workers, which may be due to neurotransmitter alteration [9,10]. Experimental studies have also shown that BaP exposure in animals induces some AD-like behavior/pathological changes, such as deficits in short-term memory in C57BL/6 J mice [11], accumulation of Aβ42 and neurodegeneration in adult Zebrafish [12], Aβ-related mRNA levels change [13], or tau hyperphosphorylation in SD rats [14].…”
Section: Introductionmentioning
confidence: 99%